The effect of playing a curriculum for the development of language communication for children People with autism spectrum - Ali, Suha (Journal of Physical Education, 2011)
The autism one of the categories of special education that have been identified in the recent increased attention in recent times. With this disorder in all its aspects starting from what it is, definitions and through different kinds of reasons that still are not resolved Some believe it causes back to the environment, parents and others attributed the causes of genetic. Since this category represents the percentage is low in any society, an urgent need for further research and studies in all the areas that interested them, and in the academic field still need a lot to get to the range, which can build on it in the numbers of the form is hoped in particular that in the case lack of attention to them, that affect them and decreases the chances of integration in society and thus detract from their ability to self-autonomy, which is basically the purpose of special education programs in general. Autistic children suffer from a deficit in language use and development, in the case of its existence, it is a repetition of what others say, they are in one way or another, they have limitations in the development of spoken language and is spoken and they urgently need to develop these skills. The present study aimed to take advantage of playing as a means to communicate with autistic children and the development of communication skills, and prepare an educational program for them that contains a collection activities, educational develop communication skills and therefore knowledge of the effectiveness of the program on them. Research was conducted on a sample of (10) Autistic children simple (spectral) age (4-6 years) at the Institute aimed to unite and diagnosed by a specialist doctor has chosen this category for being the class are to learn. The most important results is the presence of statistically significant differences between pre and post tests and the post test of the research sample.